A water- and heat-resistant, sulfur-resistant CO oxidation monolithic catalyst and a method for preparing the same
Patent Information
- Application Number
- CN202410059312.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-16
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-01-16
AI Technical Summary
[0007]为了解决现有技术中真实工况下,由于SO2和H2O的存在导致CO氧化催化剂活性和稳定性差、易中毒的技术问题,本发明提供了一种耐水热、抗硫的CO氧化整体型催化剂及其制备方法,所述整体型催化剂在90~650℃、0~10000ppmCO、0~25vol.%H2O和0~600ppm含硫物种的工况下,CO消除效率高、稳定性好,不仅具有很好的净化消除CO能力,并且具有很好的耐水、耐硫性能
[0048](1)本发明提供的耐水热、抗硫的CO氧化整体型催化剂,不仅可以在低至103℃实现对CO废气的净化消除效率达到98%以上,且经过500℃、10vol.%H2O和0~600ppm含硫分子处理后,可以在低至106℃实现对含水蒸气和SO2的CO废气的净化消除率达到98%以上,表现出了优异的CO净化消除能力和耐水热抗硫中毒能力;
Smart Images

Figure BDA0004665863650000131 
Figure BDA0004665863650000141
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmental catalysis technology, and in particular relates to a hydrothermal-resistant and sulfur-resistant monolithic CO oxidation catalyst and its preparation method. Background Technology
[0002] CO is a flammable and explosive gaseous pollutant. When a person is exposed to air with a CO concentration of 448 ppm, dizziness and vomiting will occur within two hours; when the CO concentration reaches ~1.2%, it can cause death within 1 to 3 minutes. CO is produced by the incomplete combustion of carbon-containing fuels such as coal and oil, mainly from industrial flue gas emissions, including those from the power industry and non-power industries such as steel, cement, and ceramics. Taking the steel industry as an example, CO emissions from sintering machines account for approximately 22% of the total CO emissions from steel plants, severely polluting the environment and atmosphere. CO elimination has become an important research direction in current environmental protection. Currently, mature methods for treating carbon monoxide include absorption, incineration, and catalytic oxidation. Among them, catalytic oxidation has been widely used due to its advantages of simple equipment, ease of operation, and high removal efficiency. For carbon monoxide-containing gases with relatively low concentrations, CO can be oxidized to CO2 at lower temperatures under the action of a catalyst. This method does not require the construction of complex equipment, has relatively low operating costs, and is an economical choice.
[0003] Since researchers first discovered in the 1930s that transition metal oxides promote the oxidation of CO, noble metal, non-noble metal, molecular sieve, and alloy catalysts have emerged. The most studied are non-noble metal (oxides) and noble metal catalysts. Regarding non-noble metal catalysts, the main types are Cu, Mn, and Co oxides and their composite oxides, which exhibit variable valence. The reaction proceeds according to a redox mechanism, generally requiring high temperatures and being highly susceptible to deactivation by water vapor, carbon dioxide, and sulfides. This is primarily because CO2 can competitively adsorb CO on the oxide surface and react to form difficult-to-decompose carbonates, thus inhibiting O2 migration. H2O-induced deactivation is mainly due to the formation of hydroxyl groups on the oxide surface after water adsorption, which block active sites and limit CO adsorption and reaction at the active interface. Sulfide-induced catalyst deactivation is mainly due to the reaction with non-noble metal oxides to form metal sulfides or sulfates, altering the catalyst properties and rendering it ineffective. For example, the most widely used non-precious metal room-temperature elimination catalyst is the Hogarat catalyst, which is a copper-manganese type mixed oxide. This catalyst has good low-temperature activity, but it deactivates quite quickly when exposed to water vapor.
[0004] Among precious metals, a typical example is supported gold (Au) catalysts, which can achieve complete CO elimination at around 0°C. However, their catalytic activity for CO oxidation varies significantly depending on the preparation method, pretreatment conditions, and support type. This is because the number and properties of active sites in such catalysts cannot yet be effectively controlled, thus hindering large-scale practical application. Pd catalysts exhibit high activity for the oxidation of CO and hydrocarbons, but their activity gradually decreases with increasing calcination temperature. Surface analysis confirms that high-valence Pd species on the catalyst surface are gradually reduced to low-valence species as the reaction proceeds, and the decrease in catalyst activity is related to species reduction. Furthermore, for precious metal-based catalysts in CO oxidation and elimination, the poisoning effects of components such as SO2 and H2O under real-world conditions limit their application. Currently, catalysts used for CO oxidation and elimination in industrial flue gas suffer from poor activity and stability, and are prone to poisoning. The hydrothermal resistance and sulfur resistance of precious metal catalysts urgently need improvement.
[0005] Currently, there are relevant patents for catalysts used for CO oxidation and elimination both domestically and internationally. For example, patent CN111282581A discloses a low-temperature, low-content CO catalytic combustion catalyst composition, which uses porous activated alumina as the active support and copper oxide, zinc oxide, and manganese dioxide as active components. However, its anti-sulfur and hydrothermal resistance properties are not described. Patent CN111686745A discloses a honeycomb CO, SO2, and NO... x Synchronous removal catalyst and its preparation method: the catalyst is prepared by extrusion method, the support is γ-Al2O3 nanotubes, and the active component is La. 0.7 Sr 0.3 Co x Fe 1-x O3 perovskite exhibits excellent catalytic activity and anti-poisoning properties in the 300–400℃ range, but its operating temperature is relatively high; Patent CN111437814A discloses a tin-doped platinum-titanium catalyst, its preparation method, and its applications. x Ti 1-x O2 catalyst support, then impregnated with Sn x Ti 1-x Noble metal Pt is loaded onto the surface of an O2 support to obtain Pt / Sn x Ti 1-xAn O2 catalyst, consisting of three components forming a rutile solid solution structure, exhibits good CO oxidation performance and resistance to water and sulfur poisoning. Patent US11130116B2 discloses an integral sulfur-resistant catalyst system comprising a platinum-containing active noble metal catalytic material and a zirconia sulfur-resistant support material with silica on its surface. The alumina component is introduced as a binder, with a maximum dosage not exceeding 10 wt.% of the catalyst coating. Therefore, the interaction between platinum and other active noble metals and this support is weak, negatively impacting its catalytic oxidation capacity and sulfur resistance. Furthermore, the patent does not disclose the specific preparation method of its catalyst support, and it can be used for CO catalytic oxidation at temperatures above 200°C. No hydrothermal resistance test was conducted, making it impossible to determine the effectiveness of the catalyst described in this patent for CO elimination under sulfur-containing and water vapor-containing conditions.
[0006] The information disclosed in this background section is intended only to enhance the understanding of the overall background of the invention and should not be construed as an admission or in any way implying that the information constitutes prior art known to those skilled in the art. Summary of the Invention
[0007] To address the technical problems of poor activity and stability of CO oxidation catalysts and susceptibility to poisoning due to the presence of SO2 and H2O under real-world operating conditions in existing technologies, this invention provides a hydrothermal and sulfur-resistant monolithic CO oxidation catalyst and its preparation method. The monolithic catalyst exhibits high CO elimination efficiency and good stability under operating conditions of 90–650℃, 0–10000 ppm CO, 0–25 vol.% H2O, and 0–600 ppm sulfur-containing species. It not only possesses excellent CO purification and elimination capabilities but also exhibits excellent water and sulfur resistance.
[0008] To achieve the above objectives, the present invention provides a hydrothermal and sulfur-resistant monolithic CO oxidation catalyst, wherein the catalyst powder comprises powder A, powder B, and a binder;
[0009] The powder A includes a carrier, an active component, and additives;
[0010] The carrier of powder A is an alumina-based composite oxide A (M1N1O). x -Al2O3), where M1O x N1O x It is one or more of silicon oxide, lanthanum oxide, nickel oxide, barium oxide, magnesium oxide, zirconium oxide, or calcium oxide; the total mass fraction of the alumina-based composite oxide A is 100%, the mass fraction of Al2O3 is 75% to 95%, and the balance is M1O. x and N1O x ;
[0011] The active component of the powder A is one or more of Pt, Pd, and Ru; the mass ratio of Ru to Pt (Ru / Pt) is 0 to 0.3, the mass ratio of Pd to Pt (Pd / Pt) is 0 to 0.1, and the mass ratio of the sum of the masses of Pt and Ru to the mass of Pd ((Pd+Ru) / Pt) is 0 to 0.3.
[0012] The powder B includes a carrier, active components, and additives;
[0013] The carrier of powder B is titanium dioxide-based composite oxide B (M2N2O). x -TiO2), where M2O x N2O x It is two or more of cobalt oxide, tungsten oxide, molybdenum oxide, or nickel oxide; preferably, the M2O x Molybdenum oxide, N2O x The titanium dioxide-based composite oxide B is cobalt oxide; the total mass fraction of the titanium dioxide-based composite oxide B is 100%, of which the mass fraction of TiO2 is 2-30%, and the balance is M2O. x and N2O x The mass ratio of molybdenum oxide to cobalt oxide is 1:1 to 1:10.
[0014] The active component of powder B is one or both of Pt and Ru; the mass ratio of Pt to Ru (Pt / Ru) is 0 to 1.5.
[0015] The additives for powder A or powder B are selected from one or more of lanthanum oxide, tin oxide, calcium oxide, copper oxide, potassium oxide, sodium oxide, or magnesium oxide; preferably, the additive components are cerium oxide, copper oxide, magnesium oxide, or sodium oxide; preferably, the additive components, in oxide form, account for 0.05% to 3% of the mass of powder A or powder B.
[0016] In one or more embodiments of the present invention, the binder component of the catalyst powder is selected from one or more of clay, starch, dilute nitric acid, dilute sulfuric acid, dilute phosphoric acid, methylcellulose, polyethylene glycol, and polyvinyl alcohol.
[0017] In one or more embodiments of the present invention, the amount of precious metal loaded per liter of catalyst powder is 0.1 to 5.0 g.
[0018] In one or more embodiments of the present invention, the active components of powder A are Ru and Pt, and the mass ratio of Ru to Pt (Ru / Pt) is 0.05 to 0.3, preferably 0.1.
[0019] In one or more embodiments of the present invention, the active components of powder B are Pt and Ru; the mass ratio of Pt to Ru (Pt / Ru) is 0.05 to 0.5, preferably 0.1.
[0020] In one or more embodiments of the present invention, the carrier of powder B is titanium dioxide-based composite oxide B (M2N2O). x In TiO2), M2O x Preferably, molybdenum oxide, wherein the N2O x Cobalt oxide is preferred, and more preferably, M2O x and N2O x The mass ratio is 1:1 to 1:5.
[0021] In a second aspect, the present invention provides a method for preparing a carrier for powder A, a method for preparing a carrier for powder B, a method for preparing the catalyst powder, and a method for preparing the shaped catalyst.
[0022] In one or more embodiments of the present invention, the carrier alumina-based composite oxide A (M1N1O) of powder A x The preparation method of Al2O3 includes the following steps: adding a certain amount of M1 source or N1 source to deionized water or ethanol to prepare solution I; adding a certain amount of Al source to deionized water or ethanol solution to prepare solution II; slowly adding solution II to solution I and stirring evenly to obtain solution III; adding a certain amount of pore-forming agent to solution III and stirring for 3-8 hours, or adding a pH adjuster to adjust the pH value of solution III to 8-12 and reacting for 4-8 hours; filtering; drying the obtained powder at 120℃ for 10 hours; heating to 500℃ at a rate of 5℃ / min; calcining at 500℃ for 6 hours to obtain alumina-based composite oxide A; wherein the pH adjuster is selected from ammonia, sodium hydroxide, sodium carbonate or urea.
[0023] In one or more embodiments of the present invention, the carrier of powder A is an alumina-based composite oxide A (M1N1O) x In the preparation of Al2O3, the Al source is selected from alumina, aluminum sol, aluminum nitrate, aluminum isopropoxide, or boehmite; preferably, the Al source is alumina, aluminum nitrate, aluminum isopropoxide, or boehmite; the Si source is selected from silicon oxide, tetraethyl orthosilicate, silica sol, sodium silicate, water glass, or tetramethylsilane; preferably, the Si source is tetraethyl orthosilicate, silica sol, or tetramethylsilane; the La source is selected from lanthanum oxide, LaCl3, or lanthanum nitrate; preferably, the La source is lanthanum oxide or lanthanum nitrate; the Ba source is selected from barium oxide, BaCl2, or barium nitrate; preferably, the Ba source is barium oxide or barium nitrate; the Ni source is selected from nickel oxide, nickel acetate, NiCl3, or NiCl2.2、 The source is either nickel sulfate or nickel nitrate; preferably, the Ni source is nickel sulfate or nickel nitrate; the Mg source is selected from magnesium oxide, MgCl2, or magnesium nitrate; preferably, the Mg source is magnesium oxide or magnesium nitrate; the Zr source is selected from zirconium oxide, zirconium isopropoxide, zirconium oxynitrate, zirconium nitrate, or zirconium silicate; preferably, the Zr source is zirconium oxide, zirconium isopropoxide, or zirconium nitrate; the Ca source is selected from calcium oxide, CaCl2, calcium carbonate, or calcium nitrate; preferably, the Ca source is calcium carbonate or calcium nitrate.
[0024] In one or more embodiments of the present invention, the carrier of powder B is titanium dioxide-based composite oxide B (M2N2O). x The preparation method of (-TiO2) includes the following steps: adding a certain amount of M2 source or N2 source to deionized water or ethanol to prepare solution I; adding a certain amount of Ti source to deionized water or isopropanol solution to prepare solution II; slowly adding solution II to solution I and stirring evenly to obtain solution III; adding a certain amount of pore-forming agent to solution III and stirring for 3-8 hours, or adding a pH adjuster to solution III to adjust the pH value of the solution to 9-10 and reacting for 4-8 hours; filtering, drying the obtained powder at 120℃ for 10 hours, heating to 550℃ at a rate of 5℃ / min, and calcining at 550℃ for 6 hours to obtain titanium oxide-based composite oxide carrier B; the pH adjuster is selected from ammonia, sodium citrate or sodium bicarbonate.
[0025] In one or more embodiments of the present invention, the carrier of powder B is titanium dioxide-based composite oxide B (M2N2O). x In the preparation method of TiO2, the Ti source is selected from one of titanium oxide, titanic acid, titanium isopropoxide, tetrabutyl titanate, titanium sulfate, titanium oxysulfate, or titanium tetrachloride; preferably, the Ti source is titanic acid, titanium isopropoxide, or tetrabutyl titanate; the Co source is selected from one of cobalt oxide, CoCl2, cobalt sulfate, cobalt carbonate, or cobalt nitrate; preferably, the Co source is cobalt oxide, cobalt sulfate, or cobalt nitrate; the W source is selected from one of tungsten oxide, WCl6, ammonium paratungstate, ammonium metatungstate, or phosphotungstic acid; preferably, the W source is ammonium paratungstate, ammonium metatungstate, or phosphotungstic acid; the Mo source is selected from molybdenum oxide, Na2MoO2, or NaCl2. 4、 One of phosphomolybdic acid, ammonium tetramolybdate, or ammonium heptamolybdate; preferably, the Mo source is phosphomolybdic acid or ammonium heptamolybdate; the Ni source is selected from nickel oxide, nickel acetate, or NiCl₂. 2、 One of nickel sulfate or nickel nitrate; preferably, the Ni source is nickel sulfate or nickel nitrate;
[0026] In one or more embodiments of the present invention, a certain amount of pore-forming agent is added to the alumina-based composite oxide carrier A or the titanium dioxide-based composite oxide B during preparation; the pore-forming agent is one of carbon black, glycine, citric acid, sodium citrate, tetrapropylammonium hydroxide, ammonium citrate, alanine, P123 or hexadecyltrimethylammonium bromide; preferably tetrapropylammonium hydroxide.
[0027] In one or more embodiments of the present invention, the method for preparing the catalyst powder includes the following steps:
[0028] (1) Add Pt salt and / or Pd salt and / or Ru salt, as well as metal salts as auxiliary components, to deionized water to prepare a precious metal solution.
[0029] (2) Add the carrier alumina-based composite oxide A of powder A to the noble metal salt solution, control the temperature at 25-120℃, and add a reducing agent with a molar ratio of 0-20 to the noble metal while stirring thoroughly. Dry the obtained sample and then heat it to 250-650℃ at a heating rate of 5℃ / min and calcine it for 4-10h to obtain powder A.
[0030] (3) Add the carrier titanium oxide-based composite oxide B of powder B to the noble metal salt solution, control the temperature at 25-120℃, and add a reducing agent with a molar ratio of 0-5 to the noble metal while stirring thoroughly. Dry the obtained sample and then heat it to 400-800℃ at a heating rate of 5℃ / min and calcine it for 4-10h to obtain powder B.
[0031] (4) Mix the powder A prepared in step (2), the powder B prepared in step (3), and the binder, add deionized water, and ball mill or knead thoroughly to obtain a slurry. After drying the slurry, heat it to 400-650°C at a heating rate of 5°C / min and calcine it for 4-8 hours to obtain the catalyst powder.
[0032] The mass percentage of precious metals in the catalyst powder obtained in step (4) is 0.5-5%.
[0033] In step (4), the mass ratio of powder B to powder A is 0.02-0.2:1; preferably, the mass ratio of powder B to powder A is 0.06-0.12:1.
[0034] In step (4), the ratio of the mass of the adhesive to the sum of the masses of powder A and powder B is 0-0.35:1;
[0035] In step (1), the precursor of the active component is one or more of the chlorate, nitrate or acetate of Pt, Pd and Ru; preferably, the precursor of the active component is platinum nitrate, palladium nitrate, palladium acetate or ruthenium nitrate.
[0036] In step (1), the precursor of the auxiliary component is one or more of lanthanum salt, tin salt, calcium salt, potassium salt, sodium salt or magnesium salt; the lanthanum salt, calcium salt, potassium salt, sodium salt and magnesium salt as precursors are all nitrates, and the tin salt is one of sodium stannate, tin chloride or stannous chloride.
[0037] The reducing agent in step (2) or step (3) is one of formaldehyde solution, citric acid, sodium formate or sodium borohydride;
[0038] The adhesive used in step (4) is selected from one or more of clay, starch, dilute nitric acid, dilute sulfuric acid, dilute phosphoric acid, methylcellulose, polyethylene glycol, and polyvinyl alcohol.
[0039] In step (2), the drying temperature of powder A is 80-110℃, the calcination temperature is 300-450℃, and the calcination time is 4-6h.
[0040] In step (3), the drying temperature of powder B is 90-120℃, the calcination temperature is 450-600℃, and the calcination time is 6-8h.
[0041] In step (4), the drying temperature of the catalyst powder is 90-120℃, the calcination temperature is 450-600℃, and the calcination time is 6-8h.
[0042] In one or more embodiments of the present invention, the method for preparing the monolithic catalyst includes the following steps:
[0043] The catalyst powder and binder are mixed and then added to deionized water. The mixture is then ball-milled or kneaded to obtain a slurry. The slurry is coated onto a honeycomb or spherical support, and the mass of the slurry is 10-25% of the mass of the support. After drying, the temperature is increased to 150-300°C at a rate of 10°C / min and held for 3-5 hours. Then, the temperature is increased to 450-600°C at a rate of 5°C / min and calcined for 4-8 hours to obtain the monolithic catalyst.
[0044] The mass ratio of the catalyst powder to the binder is 1:0.01-1, preferably 1:0.05-0.15;
[0045] The adhesive is selected from one or more of clay, starch, dilute nitric acid, dilute sulfuric acid, dilute phosphoric acid, methylcellulose, polyethylene glycol, and polyvinyl alcohol;
[0046] In a third aspect, the present invention provides the application of the monolithic catalyst in the purification and elimination of CO, wherein at a temperature above 100°C, 1L of the monolithic catalyst can be used to treat 5000L to 30000L of CO-containing gas in 1 hour, wherein the volume fraction of CO in the CO-containing gas is 0 to 10000ppm.
[0047] Compared with the prior art, the present invention has the following superior technical effects:
[0048] (1) The hydrothermal and sulfur-resistant monolithic CO oxidation catalyst provided by the present invention can not only achieve a purification and elimination efficiency of more than 98% for CO waste gas at a temperature as low as 103℃, but also achieve a purification and elimination rate of more than 98% for CO waste gas containing water vapor and SO2 at a temperature as low as 106℃ after treatment with 500℃, 10 vol.% H2O and 0-600 ppm sulfur-containing molecules. It shows excellent CO purification and elimination ability and hydrothermal and sulfur poisoning resistance.
[0049] (2) The monolithic CO oxidation catalyst with water and heat resistance and sulfur resistance provided by the present invention is composed of powder A, powder B, additives and binders. The catalyst prepared by powder A or powder B alone has poor CO purification capacity, poor water and heat resistance or poor sulfur resistance. The catalyst prepared by mixing powder A and powder B not only has excellent CO purification and elimination capacity, but also has good water and heat resistance and sulfur resistance.
[0050] (3) The hydrothermal and sulfur-resistant monolithic CO oxidation catalyst provided by this invention comprises Pt, Pd, and Ru in the catalyst powder as active components, which can decompose and eliminate CO; silicon oxide, lanthanum oxide, nickel oxide, barium oxide, magnesium oxide, zirconium oxide, or calcium oxide in powder A have good ability to stabilize the structure of oxides such as alumina and improve the acidity and alkalinity of the alumina surface, thereby improving the dispersion of noble metal components and reducing the influence of water vapor on the physicochemical properties of alumina and other oxides such as surface composition, crystal phase, crystal form, and pore structure; cobalt oxide, tungsten oxide, molybdenum oxide, or nickel oxide in powder B can help improve the catalyst's ability to adsorb, convert, and remove sulfur-containing molecules from the catalyst surface, and the doping of titanium oxide can... This provides a larger specific surface area, thereby improving the catalyst's ability to eliminate CO while maintaining the stability of the physicochemical properties of the active components during the reaction process. Using a mixture of two powders as the catalyst powder not only ensures that the catalyst powder support still has a high specific surface area under the condition of multiple oxides coexisting, but also fully utilizes the advantages of a single powder in eliminating CO, resisting hydrothermal or sulfur resistance. At the same time, it can reduce the competitive adsorption between CO, sulfide molecules and H2O on the catalyst surface, and facilitate the rapid transfer and removal of H2O and SO2 molecules on the support surface, reducing their damage to the support structure and the microstructure of the active center, and effectively improving the stability of the catalyst under conditions of high temperature and high water vapor.
[0051] (4) The hydrothermal and sulfur-resistant monolithic CO oxidation catalyst provided by the present invention is composed of two catalyst powders. It has a high specific surface area and a rich and well-developed pore structure. Combined with the synergistic effect between the powders, it can not only achieve efficient purification of CO, but also maintain the stability of the physicochemical properties of the catalyst after being subjected to high water vapor concentration and sulfur-containing gas treatment, thus ensuring the stability of the catalyst's performance in the CO waste gas purification and elimination process. Detailed Implementation
[0052] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.
[0053] Example 1
[0054] Preparation of alumina-based composite oxide carrier A: 26.58g of lanthanum nitrate was added to 500ml of deionized water to prepare solution D, and 294g of aluminum nitrate was added to 100ml of deionized water to prepare solution E. Solution E was slowly added to solution D and stirred until homogeneous to obtain solution F. 15g of tetrapropylammonium hydroxide was added to solution F, and sodium carbonate was added to adjust the pH of solution F to 10. The reaction was carried out for 6 hours. The solution was filtered, and the resulting powder was dried at 120℃ for 10 hours. The temperature was increased to 500℃ at a rate of 5℃ / min, and calcined at 500℃ for 6 hours to obtain alumina-based composite oxide carrier A.
[0055] Preparation of titanium dioxide-based composite oxide support B: 47.5 g of titanium tetrachloride was added to 500 ml of ethanol to prepare solution J. 16 g of ammonium heptamolybdate and 205 g of cobalt nitrate were added to 100 ml of ethanol to prepare solution K. Solution K was slowly added to solution J and stirred until homogeneous to obtain solution L. 15 g of tetrapropylammonium hydroxide was added to solution L, and sodium citrate was added to adjust the pH of solution L to 9.5. The reaction was carried out for 6 h. The solution was filtered, and the resulting powder was dried at 120 °C for 10 h. The temperature was increased to 550 °C at a rate of 5 °C / min, and calcined at 550 °C for 6 h to obtain titanium dioxide-based composite oxide support B.
[0056] Preparation of powder A: 0.82g of platinum nitrate, 0.16g of ruthenium nitrate, and 0.14g of sodium nitrate were added to 60ml of deionized water to prepare a solution. 29.4g of the above-mentioned composite oxide carrier A was added to the solution and stirred for 4h. 5.0g of sodium formate was added and reacted for 6h. The mixture was filtered and the resulting powder was dried at 120℃ for 10h. The temperature was increased to 500℃ at a heating rate of 5℃ / min and calcined at the target temperature for 4h to obtain powder A.
[0057] Preparation of powder B: 1.57g of ruthenium nitrate, 0.08g of platinum nitrate, and 0.18g of magnesium nitrate were added to 60ml of deionized water to prepare a solution. 29.4g of the above-mentioned composite oxide carrier B was added to the solution and the mixture was stirred for 6h. The mixture was then filtered and dried at 120℃ for 10h. The temperature was increased to 550℃ at a rate of 5℃ / min and calcined at the target temperature for 4h to obtain powder B.
[0058] Preparation of catalyst powder: Powder A and B prepared according to the above method and dilute sulfuric acid are mixed in a ratio of 1:0.08:0.2 and deionized water is added. The mixture is then fully ball-milled or kneaded to obtain a slurry. After drying the slurry, the temperature is increased to 550°C at a heating rate of 5°C / min and calcined at the target temperature for 6 hours to obtain catalyst powder that can be used for CO purification and elimination.
[0059] Preparation of the monolithic catalyst: 30.0 g of the catalyst powder and 1.0 g of concentrated sulfuric acid were added to deionized water and ball-milled for 2 hours to obtain a slurry. This slurry was then placed on a cordierite ceramic honeycomb carrier. The slurry is coated on a 300-mesh screen, with a precious metal content of 3000 g / m². 3 The temperature was increased to 300℃ at a heating rate of 5℃ / min and held for 3 hours; then, the temperature was increased to 550℃ at a heating rate of 5℃ / min and held for 8 hours to obtain the monolithic catalyst, denoted as Cat-1.
[0060] Example 2
[0061] Based on Example 1, in the preparation of alumina-based composite oxide A, lanthanum nitrate was replaced with barium nitrate, the mass stoichiometry of Al2O3 in composite oxide A remained unchanged, the mass stoichiometry of barium nitrate was the same as that of lanthanum nitrate, and other operations were the same as in Example 1, resulting in an integral catalyst, denoted as Cat-2.
[0062] Example 3
[0063] Based on Example 1, in the preparation of alumina-based composite oxide A, aluminum nitrate was replaced with boehmite, the stoichiometric ratio of lanthanum oxide in composite oxide A remained unchanged, and other operations were the same as in Example 1, resulting in an integral catalyst, denoted as Cat-3.
[0064] Example 4
[0065] Based on Example 1, in the preparation of powder A, the mass of ruthenium nitrate in the noble metal solution was replaced by 0.47g instead of 0.16g, and in the preparation of powder B, the mass of ruthenium nitrate was replaced by 0.31g instead of 1.57g. The rest was the same as in Example 1, and a monolithic catalyst was obtained, denoted as Cat-4.
[0066] Example 5
[0067] Based on Example 1, when preparing titanium oxide-based composite oxide B, 205g of cobalt nitrate was replaced with 220g of nickel nitrate, the mass percentage of TiO2 in composite oxide B remained unchanged, and other operations were the same as in Example 1, resulting in an integral catalyst, denoted as Cat-5.
[0068] Example 6
[0069] Based on Example 1, the amount of cobalt nitrate used in the preparation of titanium oxide-based composite oxide B was adjusted to 210g, the amount of ammonium heptamolybdate was adjusted to 14.2g, the stoichiometric ratio of TiO2 in composite oxide B remained unchanged, and other operations were the same as in Example 1, resulting in an integral catalyst, denoted as Cat-6.
[0070] Example 7
[0071] Based on Example 1, in the preparation of powder A, the mass of platinum nitrate in the noble metal solution was replaced from 0.82g to 0.86g, and the mass of ruthenium nitrate was replaced from 0.16g to 0.08g; at the same time, in the preparation of titanium dioxide-based composite oxide B, the amount of cobalt nitrate was adjusted to 126g, and the amount of ammonium heptamolybdate was adjusted to 42.6g. In the preparation of powder B, the mass of platinum nitrate was replaced from 0.08g to 0.04g, and the mass of ruthenium nitrate was replaced from 1.57g to 1.64g. Other operations were the same as in Example 1, resulting in an integral catalyst, denoted as Cat-7.
[0072] Example 8
[0073] Based on Example 1, during the preparation of powder A, ruthenium nitrate was replaced with 0.11g palladium nitrate in the noble metal solution, and other operations were the same as in Example 1, resulting in an integral catalyst, denoted as Cat-8.
[0074] Example 9
[0075] Based on Example 1, in the preparation of powder B, ruthenium nitrate in the noble metal solution was replaced with 1.08g palladium nitrate, and other operations were the same as in Example 1, resulting in an integral catalyst, denoted as Cat-9.
[0076] Example 10
[0077] Based on Example 1, titanium tetrachloride was replaced with titanium sulfate, and other operations were the same as in Example 1, resulting in a monolithic catalyst, denoted as Cat-10.
[0078] Example 11
[0079] Based on Example 1, in the preparation of composite oxide A, lanthanum nitrate was replaced with nickel nitrate, and the stoichiometric ratio of Al2O3 in composite oxide A remained unchanged; in the preparation of composite oxide B, the amount of cobalt nitrate was adjusted to 273.3g, the amount of ammonium heptamolybdate was adjusted to 10.7g, the stoichiometric ratio of TiO2 in composite oxide B remained unchanged, and other operations were the same as in Example 1, resulting in an integral catalyst, denoted as Cat-11.
[0080] Example 12
[0081] Based on Example 1, the platinum nitrate in the precious metal solution was removed during the preparation of powders A and B, and other operations were the same as in Example 1, resulting in a monolithic catalyst, denoted as Cat-12.
[0082] Comparative Example 1
[0083] Based on Example 1, powder B was removed from the step of synthesizing catalyst powder, while other operations were the same as in Example 1.
[0084] Comparative Example 2
[0085] Based on Example 1, powder A was removed from the step of synthesizing catalyst powder, while other operations were the same as in Example 1.
[0086] Comparative Example 3
[0087] Based on Example 1, the platinum nitrate in the precious metal solution during the preparation of powder A was removed, and other operations were the same as in Example 1.
[0088] Comparative Example 4
[0089] Based on Example 1, the addition of M source and N source during the synthesis of composite oxide A was removed from the catalyst powder support preparation step, and other operations were the same as in Example 1.
[0090] Comparative Example 5
[0091] Based on Example 1, the addition of M source and N source during the synthesis of composite oxide B was removed from the catalyst powder support preparation step, and other operations were the same as in Example 1.
[0092] Comparative Example 6
[0093] Based on Example 1, the sodium nitrate in the precious metal solution during the preparation of powder A was removed, and other operations were the same as in Example 1.
[0094] Comparative Example 7
[0095] Based on Example 1, magnesium nitrate was removed from the precious metal solution during the preparation of powder B, and other operations were the same as in Example 1.
[0096] Comparative Example 8
[0097] Based on Example 1, ruthenium nitrate in the precious metal solution during the preparation of powder B was removed, and other operations were the same as in Example 1.
[0098] Comparative Example 9
[0099] Based on Example 1, in the preparation of titanium oxide-based composite oxide B, cobalt nitrate was replaced with cerium nitrate, the stoichiometric ratio of TiO2 in composite oxide B remained unchanged, and other operations were the same as in Example 1.
[0100] Verification of Examples
[0101] The activity of the monolithic catalysts obtained in Examples 1-12 and Comparative Examples 1-9 was evaluated under CO-containing gas mixture conditions. The CO concentration in the inlet gas was 3200 ppm, and the remaining gas components were air. The gas space velocity (GHSV) was 15000 h⁻¹. -1 The temperature (T) at which CO removal efficiency is ≥98% is achieved. 98 Catalytic performance is expressed as ( / ℃).
[0102] At 500℃, the water vapor concentration is 10 vol.%, the SO2 concentration is 200 ppm, and the space velocity is GHSV = 15000 h⁻¹. -1 The samples from the examples or comparative examples were aged for 10 hours under the specified conditions. The inlet gas composition consisted of a CO concentration of 3200 ppm, a water vapor concentration of 10 vol.%, an SO2 concentration of 200 ppm, and the remaining gaseous component being air. The gas hourly space velocity (GHSV) was 15000 h⁻¹. -1 The aged examples or comparative examples were tested under the specified conditions to determine the temperature at which the CO purification efficiency was ≥98% (T after aging). 98 The resistance to water, heat and sulfur is expressed as / ℃.
[0103] The test results are shown in Table 1.
[0104] Table 1. CO catalytic performance and resistance to sulfur poisoning and hydrothermal activity of the monolithic catalyst of this invention.
[0105]
[0106]
[0107] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations. The scope of the invention is intended to be defined by the claims and their equivalents.
Claims
1. A hydrothermal-resistant and sulfur-resistant monolithic catalyst for CO oxidation, characterized in that, The catalyst powder includes powder A, powder B, and a binder; The powder A includes a carrier, an active component, and additives; The carrier of powder A is an alumina-based composite oxide A, namely M1N1O. x -Al2O3, where M1O x N1O x It is one of silicon oxide, lanthanum oxide, nickel oxide, barium oxide, magnesium oxide, zirconium oxide, or calcium oxide; the total mass fraction of the alumina-based composite oxide A is 100%, the mass fraction of Al2O3 is 75%~95%, and the balance is M1O. x and N1O x ; The active components of powder A are Ru and Pt; the mass ratio of Ru to Pt is 0.05~0.
3. The powder B includes a carrier, active components, and additives; The carrier of powder B is titanium dioxide-based composite oxide B, i.e., M2N2O. x -TiO2, where M2O x N2O x It is two of cobalt oxide, tungsten oxide, molybdenum oxide, or nickel oxide; the total mass fraction of the titanium oxide-based composite oxide B is 100%, the mass fraction of TiO2 is 2-30%, and the balance is M2O. x and N2O x ; The active components of powder B are Pt and Ru; the mass ratio of Pt to Ru is 0.05~0.
5. The additives for powder A and powder B are selected from one or more of lanthanum oxide, tin oxide, calcium oxide, copper oxide, potassium oxide, sodium oxide, or magnesium oxide.
2. The monolithic catalyst according to claim 1, characterized in that, The M2O x and N2O x The mass ratio is 1:1 to 1:
10.
3. The monolithic catalyst according to claim 2, characterized in that, The M2O x and N2O x The mass ratio is 1:1 to 1:
5.
4. The monolithic catalyst according to claim 1, characterized in that, The preparation method of the alumina-based composite oxide A, the carrier of powder A, includes the following steps: adding a certain amount of M1 source and N1 source to deionized water or ethanol to prepare solution I; adding a certain amount of Al source to deionized water or ethanol solution to prepare solution II; slowly adding solution II to solution I and stirring evenly to obtain solution III; adding a certain amount of pore-forming agent to solution III and stirring for 3-8 hours, or adding a pH adjuster to adjust the pH value of solution III to 8-12 and reacting for 4-8 hours; filtering; drying the obtained powder at 120℃ for 10 hours; heating to 500℃ at a rate of 5℃ / min; calcining at 500℃ for 6 hours to obtain alumina-based composite oxide A; The preparation method of the titanium dioxide-based composite oxide B, the carrier of powder B, includes the following steps: adding a certain amount of M2 source and N2 source to deionized water or ethanol to prepare solution I; adding a certain amount of Ti source to deionized water or isopropanol solution to prepare solution II; slowly adding solution II to solution I and stirring evenly to obtain solution III; adding a certain amount of pore-forming agent to solution III and stirring for 3-8 hours, or adding a pH adjuster to solution III to adjust the pH value of the solution to 9-10 and reacting for 4-8 hours; filtering; drying the obtained powder at 120℃ for 10 hours; heating to 550℃ at a rate of 5℃ / min; calcining at 550℃ for 6 hours to obtain titanium dioxide-based composite oxide B.
5. The monolithic catalyst according to claim 4, characterized in that, In the preparation method of the alumina-based composite oxide A of the carrier of powder A, the Al source is selected from one of alumina, alumina sol, aluminum nitrate, aluminum isopropoxide or boehmite.
6. The monolithic catalyst according to claim 4, characterized in that, In the preparation method of titanium oxide-based composite oxide B, which is the carrier of powder B, the Ti source is selected from one of titanium oxide, titanic acid, titanium isopropoxide, tetrabutyl titanate, titanium sulfate, titanium oxysulfate, or titanium tetrachloride.
7. The monolithic catalyst according to claim 6, characterized in that, The Ti source is titanium dioxide, titanium isopropoxide, or butyl titanate.
8. The monolithic catalyst according to claim 1, characterized in that, The method for preparing the catalyst powder includes the following steps: (1) Add Pt salt, Ru salt, and metal salt as auxiliary components to deionized water to prepare a precious metal salt solution; (2) Add the carrier alumina-based composite oxide A of powder A to the noble metal salt solution, control the temperature at 25~120℃, and add a reducing agent with a molar ratio of 0~20 to the noble metal while stirring thoroughly. The molar ratio is not 0. Dry the obtained sample and then heat it to 250~650℃ at a heating rate of 5℃ / min and calcine it for 4~10h to obtain powder A. (3) Add the carrier titanium oxide-based composite oxide B of powder B to the noble metal salt solution, control the temperature at 25~120℃, and add a reducing agent with a molar ratio of 0~5 to the noble metal while stirring thoroughly. The molar ratio is not 0. Dry the obtained sample and then heat it to 400~800℃ at a heating rate of 5℃ / min. Calcine it for 4~10h to obtain powder B. (4) After mixing the powder A prepared in step (2), the powder B prepared in step (3), and the binder, add deionized water, and fully ball mill or knead to obtain a slurry. After drying the slurry, heat it to 400~650℃ at a heating rate of 5℃ / min and calcine it for 4~8h to obtain the catalyst powder.
9. A method for preparing the monolithic catalyst according to claim 1, characterized in that, The preparation method of the monolithic catalyst includes the following steps: The catalyst powder and binder are mixed and then added to deionized water. The mixture is then ball-milled or kneaded to obtain a slurry. The slurry is coated onto a honeycomb or spherical support, and the mass of the slurry is 10-25% of the mass of the support. After drying, the temperature is increased to 150-300°C at a rate of 10°C / min and held for 3-5 hours. Then, the temperature is increased to 450-600°C at a rate of 5°C / min and calcined for 4-8 hours to obtain the monolithic catalyst.
10. The application of the monolithic catalyst prepared by the method of claim 9 in the purification and elimination of CO, characterized in that, The monolithic catalyst is used at a temperature above 100°C. 1L of the catalyst is used to treat 5000L~30000L of CO-containing gas in 1h. The volume fraction of CO in the CO-containing gas is 0~10000ppm, and the volume fraction is not 0.
Citation Information
Patent Citations
Sulfur-tolerant catalytic system
US11130116B2
Monolithic catalyst for methane combustion and preparation and application thereof
CN116099533A